The Ginger Honey And Cocktail Honey Supplementation Effect On Estradiol Hormone Levels In Female Balb/C Mice Stress-Induced Through Swimming Activities - Raya, Emmasitah, Indah (International Journal of Psychosocial Rehabilitation, 2020)
This study intends to determine the effect of Ginger Honey and Cocktail Honey on Estradiol (E2) hormone levels, and to assess the magnitude of the difference in the effects of Ginger Honey and Cocktail Honey on Estradiol levels in female Balb/c mice induced stress. A total of 25 female Balb/c mice were used in this study and were divided into 4 groups (5 in each group) with 1 control group (negative control), 2 intervention groups Ginger Honey: Ginger Honey I (containing 50% Honey: 50% ginger extract), Ginger Honey II (33% Honey: 67% ginger extract) a dose of 28mg/20gBW of mice, and Cocktail Honey Group (trigona spp. honey, royal jelly and bee bread) with the distribution of Cocktail Honey I (14mg/20gBW), Cocktail Honey II (28mg/20gBW) given 1 time/day for 14 days. Estradiol levels were examined using the ELISA kit mouse. This study was an in vivo laboratory test with a pretest-posttest design with a control group. The data were displayed as the mean and analyzed using a paired T- test. This study shows that the intervention of Ginger Honey I (50% Honey: 50% ginger extract), Ginger Honey II (33% Honey: 67% ginger extract) at a dose of 28mg/20gBW of mice, and Cocktail Honey (honey, royal jelly and bee bread) with a dose distribution Cocktail Honey I (14mg/20gBW), Cocktail Honey II (28mg/20gBW) have a positive effect and statistically have a significant value on the levels of Estradiol in female Balb/c mice induced stress when compared to control group. The statistical results both shows P<0.05. However, between both, the greatest effect on increasing levels of Estradiol is shown by the Cocktail Honey I group of 19,466 ng/ml. This study concluded that among all the intervention groups, both Ginger Honey and Cocktail Honey has great influence on the hormone Estradiol. However, Cocktail Honey I has the greatest effect on Estradiol hormone levels.